Prevalence of Borrelia burgdorferi sensu lato infection in the Czech Republic - Roman Chlibek; Jan Smetana; Kateřina Kybicová; Martina Malikova; Frederick J. Angulo; Alexandra Loew-Baselli; Ye Tan; Aleš Ondřejíček; Gordon Brestrich; Andreas Pilz; Jennifer C. Moïsi; James H. Stark (International Journal of Medical Microbiology, 2025)
Introduction: Lyme borreliosis (LB), an infection caused by Borrelia burgdorferi sensu lato (Bbsl), is the most common tick-borne disease in Europe. To further characterize the LB burden in the Czech Republic, we conducted a seroprevalence study and estimated the incidence of symptomatic Bbsl infections. Methods: Anti-Bbsl IgM and IgG antibodies were detected in sera collected from the adult population in 2011 −2012 by enzyme-linked immunosorbent assay and immunoblot tests at the National Reference Laboratory. The incidence of symptomatic Bbsl infections was estimated from the seroprevalence results and the symptomatic proportion and duration of persistence of anti-Bbsl IgG antibodies in Bbsl-infected individuals. Surveillance under-detection of symptomatic Bbsl infections was estimated by comparing surveillance-reported and seroprevalence-based incidence. Results: Samples from 1996 adults were tested; the median age (range) was 45 (18 −87) years; 1037 (52.0 %) were female. The prevalence (with 95 % confidence interval) of anti-Bbsl IgG, and IgM and/or IgG (IgM/IgG) antibodies was 6.3 % (5.3 −7.5 %), and 9.5 % (8.3 −10.9 %), respectively. The IgM/IgG prevalence was 7.8 % (6.5 −9.2 %) in Bohemia and 15.3 % (12.2 −19.0 %) in Moravia. There were an estimated 30,563 (26,550 −34,962) symptomatic incident Bbsl infections in adults in the Czech Republic in 2012, for an incidence of 352.2 (306.0 −402.9) symptomatic Bbsl infections per 100,000 adults per year. There were an estimated 11 (10 −13) symptomatic Bbsl infections for each surveillance-reported LB case in the Czech Republic in 2012. Conclusions: There is high incidence of symptomatic Bbsl infections in the Czech Republic, particularly in Moravia. Interventions are needed to address the substantial burden of LB in the Czech Republic.